4
a. {[ 5 x (5 -5 )]: 5 }+5 = [(5 x 0) : 5] + 5 = ( 0:5) + 5 = 0 +5 = 5
b. 5 x {[(5 - 5) : 5] + 5} = 5 x [(0 : 5) + 5 ] = 5 x ( 0+5) = 5 x 5 = 25
c. 5 x {[5 - (5 : 5)] + 5} = 5 x [( 5 - 1) + 5 ] = 5 x (4+5) = 5 x 9 = 45
5.
I nr - x
II-lea nr - y
III -lea nr - z
x + y + z = 1452
y = 1/2 x
y = 1/3 z
1/2 x = 1/3 y
x/2 = y/3
x= 2/3 z
inlocuim in x + y + z = 1452 in functie de z
2/3 z + 1/3 z + z = 1452
aducem la acelasi numitor comun 3
2/3 z + 1/3 z + 3/3z = 1452
6/3 z = 1452 simplificam cu 3
2 z = 1452
z = 1452/2 = 726
x = 2/3 x z = 2/3 x 726 = 2 x 242 =484
y = 1/3 x z = 1/3 x 724 = 242
verificare x + y + z = 484 + 726 + 242 = 1452